56.7k views
0 votes
Perform the indicated operation. (w 3 + 64) ÷ (4 + w)

2 Answers

0 votes
w³ + 64 = w³ + 4³ = (w+4)³ - 3*w*4(w+4) = (w+4)[(w+4)² - 12w]

(w³ + 64) ÷ (w+4)
=(w+4)[(w+4)² - 12w] ÷ (w+4)
= (w+4)² - 12w
= w² -4w + 16
User Bufei
by
5.9k points
5 votes

Answer:

The expression
(\left(w^3+64\right))/(w+4) becomes
w^2-4w+16

Explanation:

Given : Expression
(\left(w^3+64\right))/(w+4)

We have to find the simplified value of given expression.

Consider the given expression
(\left(w^3+64\right))/(w+4)

Rewrite 64 as
4^3


=w^3+4^3


\mathrm{Apply\:Sum\:of\:Cubes\:Formula:\:}x^3+y^3=\left(x+y\right)\left(x^2-xy+y^2\right)


w^3+4^3=\left(w+4\right)\left(w^2-4w+4^2\right)

Simplify,


=\left(w+4\right)\left(w^2-4w+4^2\right)

Given expression becomes,


=(\left(w+4\right)\left(w^2-4w+16\right))/(w+4)

Cancel common factors, we have,


=w^2-4w+16

Thus, The expression
(\left(w^3+64\right))/(w+4) becomes
w^2-4w+16

User James Harpe
by
6.3k points